Researching Values Methodological Approaches for Understanding Values Work in Organisations and Leadership - Espedal, Gry; Jelstad Løvaas, Beate; Sirris, Stephen; Wæraas, Arild (Springer Nature, 2022)
This open access book presents new approaches for researching values as they are performed or materialized. Values have been an important topic in academic literature for a long time; they are at the core of institutional theories and are often connected to ideals in organisations or ways of valuing. The various values-constructs are typically highlighted to underpin discussions of identity, ethos, and the purposive institutional work of leaders and employees. However, there is a need for more research on how values link and sustain actions and institutions. Contributors in this volume map and discuss useful methodological ways in which values and values work can be investigated and how research on values has been and can be applied. The chapters present different methods for collecting data, including interviews, observation and shadowing, as well as various methods for analyzing data, such as thematic, discourse and narrative analysis. Chapters also consider the role of the researcher and participant validation as a procedure to enhance the trustworthiness of the study. Finally, the book presents various empirical projects and issues related to and exemplifying values research. This book is a valuable guide for researchers and students who are looking for a practical understanding of how to research values and values work in organisations. The volume is a follow-up of the open access book, Understanding Values Work: Institutional Perspectives in Organisations and Leadership published by Palgrave Macmillan.